2021
DOI: 10.1016/j.jfo.2021.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the COVID-19 pandemic on neovascular age-related macular degeneration and response to delayed Anti-VEGF treatment

Abstract: Résumé Objectif: Étudier les effets de la pandémie de COVID-19 sur l'évolution du traitement des patients atteints de la forme néovasculaire de la dégénérescence maculaire liée à l'âge (DMLA) ayant reçu un traitement par injection anti-VEGF avec des données réelles. Méthodes: Cette étude rétrospective a été effectuée sur 116 yeux de 106 patients. Examen ophtalmique, évaluation de la meilleure acuité visuelle corrigée (MAVC), les résultats de la tomographie en cohérence optique (OCT) et le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 28 publications
3
36
1
1
Order By: Relevance
“…General guidelines on the management of nAMD were prepared after the onset of the pandemic [13,14], recommending treatment administration for every nAMD patient every two months, regardless visual functional or macular anatomical aspects, in an empirical attempt to minimize what was expected to be a mayor disaster. It is clear that this catastrophic situation has had a negative impact on functional and anatomic outcome of nAMD, as can be seen in our cohort and also in the majority the studies published in 2021 about this subject [15][16][17][18][19][20][21][22]. Even with an average delay of one month, Borrelli et al [15] found significant loss of BCVA and proportional to visit delay.…”
Section: Discussionsupporting
confidence: 66%
“…General guidelines on the management of nAMD were prepared after the onset of the pandemic [13,14], recommending treatment administration for every nAMD patient every two months, regardless visual functional or macular anatomical aspects, in an empirical attempt to minimize what was expected to be a mayor disaster. It is clear that this catastrophic situation has had a negative impact on functional and anatomic outcome of nAMD, as can be seen in our cohort and also in the majority the studies published in 2021 about this subject [15][16][17][18][19][20][21][22]. Even with an average delay of one month, Borrelli et al [15] found significant loss of BCVA and proportional to visit delay.…”
Section: Discussionsupporting
confidence: 66%
“…Yeter et al [ 29 ] in Turkey found similar results of decrease in BCVA after the lockdown in a cohort of 106 nAMD patients that didn´t received any IVI treatment or visit during the lockdown, however, the follow-up period of the study is not clear.…”
Section: Discussionmentioning
confidence: 78%
“…To our knowledge, to date, there are only a few studies analyzing the early impact of the COVID-19 outbreak on BCVA changes, due to the delay or block in retinal diseases treatments. Additionally, these studies have potential bias and limitations, such as a heterogeneous study cohort or a limited number of patients enrolled, and the different protocols adopted in countries and periods of lockdown [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…An Italian study group recently evaluated the effects of COVID-19 and its restrictions on short-term VA outcomes of eyes with nAMD and found proof of significant worsening [ 15 ]. In France, a comparable patient cohort (116 eyes in 106 patients) was analyzed for differences in VA and OCT findings after postponing treatment for nAMD [ 16 ]. They also related the negative short-term effect on VA to the treatment interruption.…”
Section: Discussionmentioning
confidence: 99%